Clinical Significances of Positive Postoperative Serum CEA and Post-preoperative CEA Increment in Stage II and III Colorectal Cancer: A Multicenter Retrospective Study - You, Weiqiang; Yan, Li; Cai, Zerong; Xie, Lei; Sheng, Nengquan; Wang, Guiyu; Wu, Xiaojian; Wang, Zhigang (Frontiers in Oncology, 2020)
Background: Carcinoembryonic antigen (CEA) is the most common serum tumor marker in colorectal cancer (CRC). Nevertheless, few previous studies demonstrated the impacts of postoperative CEA and post-preoperative CEA increment on prognosis of CRC. Methods: Patients with stage II and III CRC were included from January 2009 to December 2015. All clinical and follow-up data were collected. Patients were divided into four different groups according to the levels of postoperative serum CEA and post-preoperative CEA trends. Chi-square test was used to analyze the relationship between clinical variables and categorized postoperative CEA and CEA increment. Cox proportional hazard regression was used for univariate and multivariable analyses. The log-rank test was performed to compare PFS and OS among groups. Results: Patients, 1,008, who underwent radical surgery, were enrolled. Our results showed that positive postoperative CEA and CEA increment were related to clinical stage, T stage, N stage, tumor differentiation, and lymphatic invasion (p < 0.05). Univariate and multivariable analysis results suggested that positive postoperative CEA and CEA increment were independent prognostic factors for PFS (HR = 3.149, 95% CI, 2.426–4.088, p = 0.000 for postoperative CEA; HR = 2.708, 95% CI, 2.106–3.482, p = 0.000 for CEA increment) and OS (HR = 3.414, 95% CI, 2.549–4.574, p = 0.000 for postoperative CEA; HR = 2.373, 95% CI, 1.783–3.157, p = 0.000 for CEA increment). The survival analyses revealed positive postoperative CEA, and CEA increment predicted worse prognosis. Furthermore, our results indicated that the 3- and 5-year PFS rates were 86.6 and 78.4% in group A, but decreased to 25.3 and 7.2% in group D (p < 0.001). Similarly, the 3- and 5-year OS rates for group A were 92.5 and 83.9%, much higher than group D (p < 0.001). In other words, patients with both postoperative CEA elevation and CEA increment had the worst prognosis. Conclusions: Positive postoperative CEA and CEA increment were independent prognostic factors for stage II and III CRC. Additionally, postoperative CEA and CEA increment had significant impacts on PFS and OS of CRC.